Research Tool Design: Constructing Research Tools as Catalyst - Shahi, Sushil Kumar (Journal of NELTA Surkhet, 2015)
The purpose of this paper is to examine research tool from the analytical exploration of existing literature and views on research tool design. The paper explores and analyzes research tool in relation to research types and philosophical paradigm. Tool is explored from the restricted sense of data collection of any form on the one. On the other, tool is seen in wider range of methods, techniques and strategies of inquiry to move beyond limitation. Study design involves systematic reviews of existing literature on tool design. Secondary data and information are collected from journals, books and publications related to research methodology. Research tool design is identified as both a study design and a procedure of data collections in many forms from diverse fields. Journal of NELTA Surkhet Vol.4 2014: 91-97